2018
DOI: 10.5004/dwt.2018.22474
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on the effect of sensible heat energy storage in an inclined solar still with baffles

Abstract: a b s t r a c tThis manuscript brings out the experimental analysis on the effect of different Sensible Heat Energy Storage Materials (SHESM) in an Inclined Solar Still (ISS) attached with baffles. Experimental study was carried out under constant flow rate of water in the baffled system with different SHESM. Experimental results show that ISS with SHESM improves the yield by 57.1 and 59.5% with the polyester sheet and rubber sheet respectively as compared to the inclined solar still without any material. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…It is observed that water temperature increases linearly with the increase in the solar intensity; it reaches its maximum value when the solar intensity is maximum, and it is found to be decreased during the sunset hours. [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] The maximum hourly water temperature for the CSS, the CSSGC, the CSSBH, and the CSSGCBH is found as 61°C, 59°C, 67°C, and 65°C, respectively. The hourly water temperature is maximum for the CSSBH and minimum for the CSSGC.…”
Section: Variations Of Water and Collector Cover Temperaturementioning
confidence: 95%
“…It is observed that water temperature increases linearly with the increase in the solar intensity; it reaches its maximum value when the solar intensity is maximum, and it is found to be decreased during the sunset hours. [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] The maximum hourly water temperature for the CSS, the CSSGC, the CSSBH, and the CSSGCBH is found as 61°C, 59°C, 67°C, and 65°C, respectively. The hourly water temperature is maximum for the CSSBH and minimum for the CSSGC.…”
Section: Variations Of Water and Collector Cover Temperaturementioning
confidence: 95%
“…Any change in solar radiation affects solar distillation. Climate change or seasonal changes directly affect productivity, which has been proven by studies and real‐life experiments . Other studies were based on improving the productivity of the single slope by several simple and cheap methods .…”
Section: Introductionmentioning
confidence: 99%
“…Different review articles have been studied . Various research works have reported the use of nanofluid in solar still, the conventional solar still (CSS) with energy storage materials, inclined solar still, and hybrid solar still …”
Section: Introductionmentioning
confidence: 99%